An exploration of current сoncepts and meanings of the entrepreneurial project - N. V. Titova; S. A. Titov (Вестник университета)
A review of academic research studying the relationship between entrepreneurship and project management at the level of interpenetration of concepts, principles, methods, tools and practices has been made. The following is a description of the research methodology, which reflects different aspects of understanding the term “entrepreneurial project” and a quantitative analysis of the results of thematic coding. The results of the study have been presented. Conclusions have been formulated that include an interpretation of the findings and the maim points on how the term “entrepreneurial project” is currently understood and what trends in the development of the theory and practice of entrepreneurship and project management reflects the current understanding.